Studi Deskriptif Kuantitatif Reseliensi pada Mantan Pelaku Adiksi Narkoba - Muhammad Iqbal Firmansyah; Amalia Kartika Yani; Tiara Tri Ariani; Lidya Yuliani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to describe the level of resilience in former drug addicts and analyze its influence on their recovery and social reintegration process. Using a descriptive quantitative approach, data were collected through a questionnaire based on Grotberg’s theory consisting of 48 items. Five participants who had abstained from drugs for approximately two years were involved in this research. The results showed that most participants had high to very high levels of resilience. External factors such as family support and economic conditions, as well as internal factors like self-awareness and future-oriented motivation, significantly contributed to increased resilience. This study emphasizes the crucial role of resilience in helping former drug addicts endure challenging times and prevent relapse.